Electromagnetic launcher system prototype for non-lethal engagements: Innovation in materials and engineering for sustainable defense technologies - Simatupang, Joni Welman; Simangunsong , Evanco Hollis Pardamean (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Electromagnetic launchers specifically coil guns have gained a considerable attention as one of the potential tools for non-lethal engagements. Methods: This research will explore the potential, working principles, and calculation that purpose. Coil guns utilize magnetic field in the form of coils are used to launch a projectile at high velocity without any chemical reaction, unlike conventional firearm. Development for coil gun on non-lethal engagements are still a challenge due to the precision of impact force, device’s reliability, and more. This prototype was developed as a two-staged coil gun controlled by Arduino and using a ST41 steel projectile. The system also implements IR LED in the coil as a failsafe should the timing did not work as expected. Findings: The results that the predicted results from the testing shown that the device could be capable for non-lethal engagements because the prototype performed with a peak muzzle velocity of 15.9 m/s and did not exceed the maximum of 100 Joules of energy at impact. Conclusion: This clearly shows that with more research, this method of a launcher could be promising due to the fact that in future advancements of research, coil gun is capable of great things, especially in the segment of non-lethal engagements. Novelty/Originality of this Study: This study contributes to the field of non-lethal weapon technology by developing a two-staged coil gun prototype controlled by Arduino, demonstrating its feasibility for non-lethal engagements with a peak muzzle velocity of 15.9 m/s and impact energy below 100 Joules, while incorporating an IR LED failsafe system to enhance operational reliability.